Isolation, identification and characteristics of Aeromonas sobria from diseased rainbow trout (Oncorhynchus mykiss) - Liu, Li-Ping; Fang, Ying-Dong; Kang, Peng-Tian; Gao, Xiang-Yun; Zhang, Guo-Wei; Pan, Jing; Lu, Jia; Liu, Ji-Xing; Zhang, Wang-Dong (Frontiers in Microbiology, 2025)
Aeromonas sobria is an opportunistic pathogen that can infect humans, animals and aquatic species, which is widely distributed in different aquatic environments and products. In recent years, with the rapid expansion of intensive aquaculture, the disease caused by A. sobria has occurred. This study aims to understand the pathogenic characteristics of A. sobria and provide scientific basis for the prevention and control of the epidemic. The dominant strain As012 was isolated from the diseased rainbow trout during the outbreak. Through physiological and biochemical experiments, sequencing and phylogenetic tree analysis of 16S rRNA and gyrB genes, the strain As012 was identified as A. sobria. The clinical signs of the diseased rainbow trout in the experimental infection were consistent with those in the farm, and the LD50 was 1.0 × 106.6 CFU/mL. The histopathological lesions in the gills, heart, liver, spleen and intestines were mainly extensive hemorrhage. In addition, eight virulence genes were screened from strain As012, including Act, Aer, AexT4, Alt, ahyB, ascV, Nuc and Hly. The strain As012 can grow in the environment with pH 1–11, temperature 8–43°C and NaCl concentration 0–8%. The drug sensitivity results showed that it was resistant to 12 antibiotics including penicillin G, vancomycin, and clindamycin, and highly sensitive to 16 antibiotics including cefazolin, ciprofloxacin, and furadantin. The results showed that A. sobria, the dominant strain isolated from diseased rainbow trout, was the main pathogen causing the epidemic in the farm. The strain As012 has a very wide range of growth and strong pathogenicity, causing widespread hemorrhaging in various tissues of rainbow trout. It is multi-resistant, but highly sensitive to cephalosporins, quinolones, nitrofurans and sulfonamides. Among them, ciprofloxacin will be one of the effective antibiotics for preventing and controlling A. sobria infection in Chinese aquaculture.